COVID-19 and its effect on anatomical sciences education: viewpoint of anatomical sciences professors of Iran university of medical sciences - Mehrdad Ghorbanlou; Fatemeh Moradi; Ronak Shabani; Mehdi Mehdizadeh (مجله ایرانی آموزش در علوم پزشکی, 2021)
Letter To Editor